PENGARUH LAMA PERENDAMAN DAN KONSENTRASI NATRIUM METABISULFIT TERHADAP KANDUNGAN VITAMIN C DAN TINGKAT KECERAHAN DALAM PEMBUATAN TEPUNG UBI JALAR, TEPUNG JAGUNG DAN TEPUNG SINGKONG - Ika Okhtora Angelia; Abd. Azis Hasan (Jurnal Technopreneur (JTech), 2018)
The types of plants commonly used to making flour include tubers that have carbohydrates that resemble as wheat, are sweet potatoes, potatoes, corn, and cassava. The problem often faced by food containing carbohydrates is easy to a browning reaction because of the activity of polyphenols and oxidation enzymes which can convert polyphenols into polycarbonate insulation. The defective that causes color changes during storage can be overcome by using additives that are standard and safe for consumption such as Natrium Metabisulfite. The effect of soaking time on Natrium Metabisulfite on the whitish degree of flour will also be studied. This study was conducted to determine Vitamin C level and the whitish degree of flour in the process of making cassava flour, sweet potato flour and corn flour. The research used factorial design with three treatment combinations and each treatment was repeated three times with two factors, soaking length (15 minutes, 30 minutes , 45 minutes) and Natrium Metabisulfite concentration (1 gram , 2 gram , 3 gram). The results showed that sweet potato flour of had the highest significant effect the whitish degree of flour (treatment A3N3) and vitamin C (treatment A2N3). Soaking length and Natrium Metabisulfite had significant effect the whitish degree of flour and vitamin C.